Studying and teaching Turkic languages of the Siberian group in Ankara University - Killi Yılmaz, Gülsüm (The New Research of Tuva, 2018)
The article provides a review of the major directions of studying and teaching Turkic languages of the Siberian group at Ankara University, since the 1930s, when the first entities were set up, later to be incorporated into the Universities which was established in 1946. Ankara University was the first educational and research institution in Turkey to start teaching modern Turkic languages as separate academic disciplines and researching them. Overall, the history of Turkic language programs in Ankara can be divided into two stages. The first period began with the establishment of the university and lasted until the Department of Modern Turkish Languages and Literatures was launched in 1992. Research in Turkology began in 1936, and since 1940s the curriculum featured subjects in specific Turkic languages. The article focuses on the contributions made by professors Abdülkadir İnan (1889–1976), Saadet Çağatay (1907–1989) Hasan Eren (1919–2007). A special discussion of the foundation of a dedicated department by Professors Mustafa Canpolat and F. Sema Barutçu Özönder is also provided. This department came to be known as the Department of Modern Turkish Languages and Literatures. The second period, having begun in 1992, lasts until now. In the first years of its history, the Department of Modern Turkish Languages and Literatures had only foreigners on its staff list, including Yu.I. Vasil’yev, Ch.M. Dorzhu, M.V. Oyun, M.B. Kungaa, T.N. Borgoyakova and A.T. Tybykova. The author discusses the most important contributions these academics made in research and teaching. Also mentioned are the dissertations defended at the epartment in the 1990s and 2000s, such as those by K.M. Simçit and G. Killi, as well as the monographs and articles by researchers currently on the Department’s stafflist and the academic programs provided by the department. A special focus is made on the “Modern Türklük Araştırmaları” journal published by the university since 2004. Since 2002, a symposium in modern Turkic studies has been held by the department, with participation of researchers from various Turkish institutions. It is notable that the interest in Turkic languages, history, culture and belief systems of Turkic peoples of Siberia in Turkish academic circles is steadily growing.